Snow loads a guide to the use and understanding of the snow load provisions of ASCE 7-02 - O'Rourke, Michael J.; Wrenn, Peter D. (American Society of Civil Engineers, 2004)
Snow Loading is a frequent and costly cause of structural performance failures. In fact, snow is the controlling roof load in half of US States. As a structural engineer, you must be familiar with snow loads. This book will provide you with the tools you need to understand and compensate for snow loads in structural design. Snow Loads: A Guide to the Use and Understanding of the Snow Load Provisions of ASCE 7-02 is the only book of its kind that provides a detailed authoritative interpretation of snow load provisions of ASCE Standard 7-02. Included are examples of flat roof loads, sloped roof loads, partial loads, as well as all types of conventional drift loading. Readers will benefit from the frequently asked questions section, which addresses and demonstrates the correct implementation of the provisions of ASCE 7-02, such as unique snow loading cases and ways to mitigate drift loads on existing roofs due to new additions. This Guide is essential for practicing structural engineers. Twelve informative chapters cover: Ground Snow Load, Flat Roof Snow Loads, Sloped Roof Snow Load, Partial Loading, Unbalanced loads, Drifts on Lower Roofs, Roof Projections, Sliding Snow Loads, Rain-on-Snow Surcharge Loads, Ponding Instability and Existing Roofs, and Frequently Asked Questions. Over 70 figures and tables clearly illustrate snow load scenarios. In addition, each chapter contains numerous worked examples that will aid you in understanding and applying difficult wind loads concepts.